Advancements in genome editing tools for genetic studies and crop improvement - Ahmadikhah, Asadollah; Zarabizadeh, Homa; Nayeri, Shahnoush; Abbasi, Mohammad Sadegh (Frontiers in Plant Science, 2025)
The rapid increase in global population poses a significant challenge to food security, compounded by the adverse effects of climate change, which limit crop productivity through both biotic and abiotic stressors. Despite decades of progress in plant breeding and genetic engineering, the development of new crop varieties with desirable agronomic traits remains a time-consuming process. Traditional breeding methods often fall short of addressing the urgent need for improved crop varieties. Genome editing technologies, which enable precise modifications at specific genomic loci, have emerged as powerful tools for enhancing crop traits. These technologies, including RNA interference, Meganucleases, ZFNs, TALENs, and CRISPR/Cas systems, allow for the targeted insertion, deletion, or alteration of DNA fragments, facilitating improvements in traits such as herbicide and insect resistance, nutritional quality, and stress tolerance. Among these, CRISPR/Cas9 stands out for its simplicity, efficiency, and ability to reduce off-target effects, making it a valuable tool in both agricultural biotechnology and plant functional genomics. This review examines the functional mechanisms and applications of various genome editing technologies for crop improvement, highlighting their advantages and limitations. It also explores the ethical considerations associated with genome editing in agriculture and discusses the potential of these technologies to contribute to sustainable food production in the face of growing global challenges.